2016
DOI: 10.1111/jcpe.12495
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast VEGF‐receptor 1 expression as molecular target in periodontitis

Abstract: Based on the finding that VEGF-receptor kinase inhibition impaired collagen degradation pathways, Flt-1 may represent a candidate for therapeutic approaches in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 42 publications
2
28
0
1
Order By: Relevance
“…Three pairs of patient-matched gingival fibroblasts were isolated from periodontitis-affected and healthy gingival tissues, and designated as periodontitis-associated fibroblasts (PAFs) and non-periodontitis-associated fibroblasts (non-PAFs). Consistent with our previous report 7 , PAFs induced collagen degradation more strongly than non-PAFs in an established three-dimensional co-culture model of periodontitis ( Fig. 4(a) ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Three pairs of patient-matched gingival fibroblasts were isolated from periodontitis-affected and healthy gingival tissues, and designated as periodontitis-associated fibroblasts (PAFs) and non-periodontitis-associated fibroblasts (non-PAFs). Consistent with our previous report 7 , PAFs induced collagen degradation more strongly than non-PAFs in an established three-dimensional co-culture model of periodontitis ( Fig. 4(a) ).…”
Section: Resultssupporting
confidence: 92%
“…Gingival fibroblasts play important roles not only in the homeostasis of gingival tissue architecture but also in the pathogenesis of periodontitis 2 . Recently, we isolated and characterized a subset of gingival fibroblasts derived from periodontitis-affected patients that were designated as periodontitis-associated fibroblasts (PAFs), and demonstrated that they were highly capable of collagen degradation 6 7 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting area of research that is often left unstudied is the effect of higher‐than‐optimal doses of growth factors on tissue remodeling. For instance, Ohshima et al 35 , 36 found certain growth factors, including TGF‐β and VEGF, are not only capable of supporting tissue regeneration but may also participate in tissue degradation in periodontitis. While in general both of these growth factors are routinely associated with tissue regrowth (TGF‐β) and angiogenesis (VEGF), it must not be excluded that they may also show negative effects.…”
Section: Discussionmentioning
confidence: 99%